Trophodynamics and health risk assessment of heavy metals in seafood from a tropical estuary in the gulf of Guinea - Abraham Ogheneruemu Ekperusi; David O Asiwa (Environmental Research, 2024)
Seafood is an essential protein source for coastal communities. However, they can accumulate heavy metals from human activities which could pose a potential health risk to consumers. In this study, we investigated the distribution, bioaccumulation, trophic transfer and potential human health risk of heavy metals in sediments, shell and fin fish collected from the Escravos Estuary in southern Nigeria. Heavy metals (Ni, Cd, V, Pb and Cu) in sediments, periwinkles and tongue soles from the two study sites were lower than the permissible limits for fishery products. The metal distribution in fish tissues was in the decreasing order of liver > gills > muscles > gonads > rest of the fish. Moderate to high BSAF (>1) was reported for Cd, Pb and Cu. All the studied metals, except Pb, showed evidence of biomagnification from periwinkle to tongue sole. The estimated daily intake (EDI) and hazard ratio (HR) for metals in periwinkles from both study sites were lower or within the USEPA reference doses (RfD) for the respective daily intake and HR value < 1, except for Cd, V and Pb for children. In contrast, EDI values in the muscle of tongue soles were higher than the RfD values for heavy metals except for Ni and Pb, whereas HR values > 1 except for Ni, Cd and V. In the whole fish, EDI and HR values were disproportionately high in both study sites with higher values reported for children. This study provides the first insights on the trophic transfer and risk assessment of heavy metals from petroleum and gas operations impacting the Escravos Estuary and the implications to public health.
Keywords: Heavy metals; Seafood; Trophic transfer; BSAF; Estimated daily intake; risk assessment